Surgical outcomes of patients with neuroblastoma in Oman: A retrospective cohort study - Salma Amur Al Khanjari; Sulaiman Said Al Saidi; Thuraiya Malik Al Harthi; Debesh Chandra Maji; Mohammed Jaffer Al Sajwani (Journal of Indira Gandhi Institute of Medical Sciences)
Background: Neuroblastoma is the most common extracranial solid tumor in pediatrics. Preexisting studies on neuroblastoma focus on epidemiological characteristics and medical treatment outcomes, leaving a gap of understanding the consequences of surgical treatment. The aim of our study was to explore the surgical interventions and their outcomes in the management of children with neuroblastoma in Oman and to determine the factors that contribute to poor surgical outcomes. Methods: Children operated for neuroblastoma for 10 years between January 2012 and June 2022 in the Royal Hospital were included in the study. Data were analyzed retrospectively and retrieved from the hospital’s electronic health records. Descriptive analysis and correlation were performed using SPSS software. Results: A total of 33 children were operated over the study period. 60.6% were males, and the mean age at diagnosis was 23.23 months. The median duration of surgery was 137 min and 147 min for nonvascular and vascular involvement, respectively. Postoperative complications were as follows: 12.12% had a fever, and 9% had an intestinal obstruction. The recurrence rate was 21.2%, and the mortality rate was 21.2%. Out of the total 10 patients with poor outcome (recurrence and/or death), 50% had stage M disease, 30% had NMYC amplification (in 40% NMYC was not done), and 70% had low vanillylmandelic acid (VMA):homovanillic acid (HVA) ratio (<1). Conclusion: Intraoperative complication rate, incomplete surgical resection, and duration of surgery correlated positively with the presence of vascular encasement. Patients with poor outcomes were more likely to have vascular encasement, incomplete resection, stage M disease, low VMA: HVA ratio and unfavorable markers. We emphasize on the importance of performing the NMYC amplification test as it is important for prognosis and planning of treatment.